A Psychoeducational Group Intervention for Siblings of Children With Autism Spectrum Disorder. Issue 4 (2nd October 2017) - Brouzos, Andreas; Vassilopoulos, Stephanos P.; Tassi, Christina
Abstract : This study examined the effectiveness of an 8-week psychoeducational group program for siblings of children with autism spectrum disorder (ASD). The sample consisted of 38 siblings aged 6–15 years ( M  = 10.75), allocated to the experimental ( n  = 22) or control group ( n  = 16). Self-report questionnaires were administered before and after the intervention. Results indicated a significant increase in knowledge of ASD in the experimental group, but not in the control group. In addition, a statistically significant reduction in adjustment difficulties and emotional/behavioral problems in the experimental group was detected. The theoretical and practical relevance of the findings for facilitating sibling support groups is discussed.